Implementasi Permissioned Blockchain Berbasis Hyperledger Sebagai Penjamin Integritas Data Pada Sistem E-Vote - Dyah Ayu Prabandari; Adhitya Bhawiyuga; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
E-vote system is a system to collect vote that involves electronic devices in order to improve the rate of voting practice, reduce the cost used, and improve the accuration in vote counting. Several researches utter that procedures which exist in current e-vote system is not enough to ensure data integrity, especially against an insider attack. Thus, this research is conducted to improve stored data integrity in data storage using permissioned blockchain where data processing and data storage are carried out in distributed manner. This research will produce an e-vote system which is integrated with permissioned blockchain using Hyperledger Fabric as the platform and Hyperledger Composer as a tool. To access the permissioned blockchain, user can utilize a node appropriate to his role in system. There are three roles in the system, that is Admin, Voter, and Operator. Application development for user's node will make use of Hyperledger Composer. Then, to know whether the system can actually protect data integrity in peer or not, some test cases will be conducted. The results of those cases show that e-vote system integrated with permissioned blockchain is capable to protect data integrity.